2017
DOI: 10.3390/rs9020165
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Rapid-Moving Reactivation of Earth Flows by Means of GB-InSAR: The April 2013 Capriglio Landslide (Northern Appennines, Italy)

Abstract: This paper presents the main results of the GB-InSAR (ground based interferometric synthetic aperture radar) monitoring of the Capriglio landslide (Northern Apennines, Emilia Romagna Region, Italy), activated on 6 April 2013. The landslide, triggered by prolonged rainfall, is constituted by two main adjacent enlarging bodies with a roto-translational kinematics. They activated in sequence and subsequently joined into a large earth flow, channelizing downstream of the Bardea Creek, for a total length of about 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…The Capriglio landslide is a large earth flow located in the Northern Apennines (Figure 5d, Table 2), which was triggered in April 2013 by prolonged rainfall and snowmelt [76,77]. The landslide is constituted by two main adjacent enlarging bodies with a roto-translational kinematics; they activated in sequence and subsequently joined into a large earth flow, channelizing downstream of the Bardea Creek for a total length of about 3600 m (Figure 14a-c).…”
Section: Aerial Irt Surveys For Landslide Ponds-drainage Network Mappmentioning
confidence: 99%
“…The Capriglio landslide is a large earth flow located in the Northern Apennines (Figure 5d, Table 2), which was triggered in April 2013 by prolonged rainfall and snowmelt [76,77]. The landslide is constituted by two main adjacent enlarging bodies with a roto-translational kinematics; they activated in sequence and subsequently joined into a large earth flow, channelizing downstream of the Bardea Creek for a total length of about 3600 m (Figure 14a-c).…”
Section: Aerial Irt Surveys For Landslide Ponds-drainage Network Mappmentioning
confidence: 99%
“…The use of this tool to monitor structures, landslides, volcanoes and sinkholes is widely documented (Calvari et al, 2016;Di Traglia, 2014;Intrieri et al, 2015;Bardi et al, 2016Bardi et al, , 2017Martino and Mazzanti, 2014;Severin et al, 2014;Tapete et al, 2013), as well as for early warning and forecasting (Intrieri et al, 2012;CarlĂ  et al, 2016a, b;Lombardi et al, 2016).…”
Section: Gb-insarmentioning
confidence: 99%
“…3D surface changes can be monitored with TLS LiDAR and GNSS [15] or SAR intensity offset tracking method with a prior deformation model [5]. Finally, continuous fast-moving deformation of earth flow can be obtained by the GB-InSAR technique [9].…”
Section: Landslide Monitoringmentioning
confidence: 99%
“…The satellite observations were validated by differential GPS time-series data and proved to be a promising method for monitoring landslides characterized by linear and relatively slow movement rates [4]. GB-InSAR was applied to track the rapid movement of earth flows over the Capriglio landslide in northern Appennines, Italy, which was re-activated in April 2013 [9]. The authors demonstrated the capability of GB-InSAR in measuring high deformation rates (~meters/days) to support local authorities in hazard assessment and risk management.…”
Section: Landslide Deformation Monitoringmentioning
confidence: 99%